Relations between Unsociability and Peer Problems in Chinese Children: Moderating Effect of Behavioural Control. Issue 1 (14th March 2014) - Ding, Xuechen; Weeks, Murray; Liu, Junsheng; Sang, Biao; Zhou, Ying
<x xml:space="preserve">Abstract</x> Unsociable children are likely to develop adjustment difficulties in Chinese society. The primary goal of the present study was to examine the moderating effect of behavioural control on the relation between unsociability and peer problems in Chinese children. Participants were fourth to eighth grade students in urban China (N = 787). Assessments of unsociability, shyness, peer problems and behavioural control were obtained from peer nominations and teacher ratings. Results indicated that unsociability was positively related to peer problems in Chinese children after controlling for shyness. Also, the relation between unsociability and peer problems was attenuated among children with higher behavioural control. Thus, behavioural control may be a buffering factor that serves to protect unsociable children from developing peer problems. Gender and age also moderated these associations. Results are discussed in terms of the meaning and implications of unsociability and behavioural control in Chinese culture. Copyright © 2014 John Wiley & Sons, Ltd.